2015
DOI: 10.5194/se-6-243-2015
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbiological properties and enzymatic activities of long-term post-fire recovery in dry and semiarid Aleppo pine (<i>Pinus halepensis</i> M.) forest stands

Abstract: Abstract. Wildfires affecting forest ecosystems and post-fire silvicultural treatments may cause considerable changes in soil properties. The capacity of different microbial groups to recolonise soil after disturbances is crucial for proper soil functioning. The aim of this work was to investigate some microbial soil properties and enzyme activities in semiarid and dry Aleppo pine (Pinus halepensis M.) forest stands. Different plots affected by a wildfire event 17 years ago without or with post-fire silvicultu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 52 publications
5
52
0
Order By: Relevance
“…Research findings confirmed that vegetation restoration as a land management option is crucial to protect diverse degraded landscapes (Gong et al, 2015), accelerate the recovery of soil-forest functions (Hedo et al, 2015) and overwhelmingly control sediment delivery to the river systems (Keesstra, 2007). Vegetation cover also facilitates soil development over time, stabilizes the direct effect of raindrops on soil, deals with surface runoff, mitigates soil erosion by stabilizing soil aggregation, improves organic carbon sequestration in the soil, and enhances soil porosity and the infiltration rate of soils and is also useful for the conservation and management of soil and water resources (Lieskovský and Kenderessy, 2014;Yu and Jia, 2014;Bruun et al, 2015;Feng et al, 2015;Gong et al, 2015;Qiang et al, 2016).…”
Section: B Gessesse Et Al: Determinants Of Farmers' Tree-planting Isupporting
confidence: 56%
“…Research findings confirmed that vegetation restoration as a land management option is crucial to protect diverse degraded landscapes (Gong et al, 2015), accelerate the recovery of soil-forest functions (Hedo et al, 2015) and overwhelmingly control sediment delivery to the river systems (Keesstra, 2007). Vegetation cover also facilitates soil development over time, stabilizes the direct effect of raindrops on soil, deals with surface runoff, mitigates soil erosion by stabilizing soil aggregation, improves organic carbon sequestration in the soil, and enhances soil porosity and the infiltration rate of soils and is also useful for the conservation and management of soil and water resources (Lieskovský and Kenderessy, 2014;Yu and Jia, 2014;Bruun et al, 2015;Feng et al, 2015;Gong et al, 2015;Qiang et al, 2016).…”
Section: B Gessesse Et Al: Determinants Of Farmers' Tree-planting Isupporting
confidence: 56%
“…Microbial biomass increases quickly in the early forest succession stage and then decreases and remains at a constant level with long-term forest restoration [10]. Hedo et al [11] reported that post-fire silvicultural treatment did not have a direct effect on soil microbial properties and soil enzyme activities. However, little is known about the response of microbial communities to the succession of vegetation after fire [12].…”
Section: Introductionmentioning
confidence: 99%
“…Zagas et al [6] obtained similar results for the "aspect" in Aleppo pine seeding, so these authors also analyzed seedling success independently of topographic conditions. In addition, our soil sampling results revealed that there were no differences between soil parameters depending on aspect because soils need a long time to recover normal activity after a fire [53].…”
Section: Discussionmentioning
confidence: 73%